Integrated Optics - Sensors, Sensing Structures and Methods - Pustelny, Tadeusz (Photonics Letters of Poland, 2016)
<!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> The current issue of the Photonics Letters of Poland contains 7 selected paper presented during the 11th Integrated Optics - Sensors, Sensing Structures and Methods Conference, which was held form February 28th to March 4th in Szczyrk, Poland. The remaining 3 papers included in this issue are regular contributions.